Supply Chain Risk Management Cases and Industry Insights - Helmold, Marc; Küçük Yılmaz, Ayşe; Dathe, Tracy; Flouris, Triant G. (Management for Professionals, 2022)
XVI, 277 p. 111 illus., 109 illus. in color.